Kreativitas dan Inovasi Pelaku Usaha dari Penciptaan Kreasi Barang Bekas di Kelurahan Kembangan Selatan Jakarta Barat - Supriyatno Supriyatno; Dewi Murtiningsih; Andriansyah Bachtillah (FKIP, Universitas Palangka Raya, 2024)
Waste is one of the problems that is quite difficult to deal with in Indonesia. This happens because of the people's habits as consumers who always produce waste. Therefore, changing used goods into goods that can be reused can help reduce environmental pollution. Waste management is one of the main challenges in achieving environmental sustainability. This community service program aims to develop a used goods creation business based on business and environmental sustainability in Kembangan Selatan Subdistrict. The methods used include outreach, training and assistance to local communities in processing used goods into economically valuable, creative and innovative products. Through this program, it is hoped that the community can improve their skills in processing waste, create new business opportunities and reduce the amount of waste generated. pollute the environment. The results of this activity show increased awareness and community participation in protecting the environment, as well as the formation of several new business groups engaged in recycling. Business sustainability is measured through indicators of increasing income and quality of life for the community. Thus, it is hoped that this program can become a business development model that is not only economically profitable, but also contributes positively to environmental sustainability.